2011
DOI: 10.1590/s1806-83242011000600004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a cordless retraction paste material on implant surfaces: an in vitro study

Abstract: Cordless retraction paste material for gingival retraction in implant dentistry has recently become of interest to the clinician. However, few studies have been conducted on the use of retraction pastes and their possible interaction with implant surfaces. This in vitro study evaluated the effect of a cordless retraction paste material, Expasyl  (Acteon), on TiUnite  (Nobel Biocare) implant surfaces. Three areas of the fixtures were evaluated before and after contact with the retraction paste using scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…Minimal alterations to surface morphology after contact with Expasyl  (Acteon) were observed in SEM images, which partially supports the findings by Chang et al 5 The only change was observed at ×5000 magnification, where "white" particles were visible on the surface. However, this was not replicated in all images of the exposed disks (Southern Implant).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Minimal alterations to surface morphology after contact with Expasyl  (Acteon) were observed in SEM images, which partially supports the findings by Chang et al 5 The only change was observed at ×5000 magnification, where "white" particles were visible on the surface. However, this was not replicated in all images of the exposed disks (Southern Implant).…”
Section: Discussionsupporting
confidence: 87%
“…After exposure to Expasyl  (Acteon), EDS measurements indicated that silicon was present, but only at levels near the instrumental detection limit, an observation consistent with the findings of Chang et al 5 Because the EDS silicon data was only con- Si/Ti, p < 0.05. sidered to be indicative, LA-ICP-MS was employed to fully quantify elemental abundances owing to its sensitivity and spatial resolution. 14 The EDS showed that titanium and some aluminium were present before the disk (Southern Implant) was exposed.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations